Labour law beyond national borders - Carta, Cinzia (Delavci in delodajalci, 2022)
The article presents an overview on the main topics analyzed in the journals belonging to the International Association of Labour Law Journals (IALLJ) throughout 2018, 2019 and 2020. As regards the subjects selected for consideration, the authors decided to focus on five topic groups that reflect the major interests shown by IALLJ scholars in the large number of articles under review. This overview is thus divided into five sections: labour law’s boundaries; responsibilities along global supply chains; challenges of trade unions in guaranteeing a minimum wage and working conditions; prohibition of discrimination and decent working conditions for women.
Keywords: delovni pogoji; delovno pravo; discriminations; diskriminacija; dobavne verige; global supply chains; labour law; labour law’s boundaries; minimalna plača; minimum wage; sindikati; trade unions; working conditions